2020
DOI: 10.1038/s41598-020-72093-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaled eutectic NiAl-(Cr,Mo) composites with exceptional mechanical properties processed by electron beam melting

Abstract: Eutectic NiAl-(Cr,Mo) composites are promising high temperature materials due to their high melting point, excellent oxidation behavior and low density. To enhance the strength, hardness and fracture toughness, high cooling rates are beneficial to obtain a fine cellular-lamellar microstructure. This can be provided by the additive process of selective electron beam melting. The very high temperature gradient achieved in this process leads to the formation of the finest microstructure that has ever been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…It can be concluded that a smaller lamella size would increase the fracture toughness. Electron beam melting might be an approach to control the lamella size, as done by Förner et al [ 38 ] In addition, the fracture toughness of the β‐NiAl phase seems to be lower than the interface strength. A ductilization of β‐NiAl can increase the fracture toughness, as the toughening mechanisms can appear at both phase transitions of the crack.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that a smaller lamella size would increase the fracture toughness. Electron beam melting might be an approach to control the lamella size, as done by Förner et al [ 38 ] In addition, the fracture toughness of the β‐NiAl phase seems to be lower than the interface strength. A ductilization of β‐NiAl can increase the fracture toughness, as the toughening mechanisms can appear at both phase transitions of the crack.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] The pre‐heating of the powder bed can cause sintering of powder particles, which can in turn enhance material's electrical conductivity and mechanical stability i.e., reduce residual stresses. [ 15 ] This explains the higher number of publications on E‐PBF printing of non‐weldable alloys such as binary intermetallic compounds, compared to the number of studies using L‐PBF. [ 14 ]…”
Section: Emerging Metals In Ammentioning
confidence: 99%
“…Previous studies have already confirmed electron beam remelting to be a suitable process for creating nanostructured in-situ composites, where immiscible eutectic systems are able to form phases smaller than 10 nm. [30] In the case of Nb-Si-Cr, the phases are also in the regime of 10 nm, but their irregular shape prohibits an accurate measurement of phase diameter. For slower scan rates (v = 250 mm/s and v = 125 mm/s), especially the Cr 2 Nb and Nb ss phases are coarser.…”
Section: Phase-specific Analysismentioning
confidence: 99%
“…[29] This study aims towards the creation of a nanostructured and aligned eutectic Nb-10.9Si-28.4Cr in-situ composite like it has been done previously for NiAl-Cr(Mo) in-situ composites. [30] Geng et al…”
Section: Introductionmentioning
confidence: 99%